2021
DOI: 10.3390/brainsci11020185
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mental Imagery in Parkinson’s Disease Rehabilitation

Abstract: Parkinson’s disease (PD) is a disabling neurodegenerative disease whose manifestations span motor, sensorimotor, and sensory domains. While current therapies for PD include pharmacological, invasive, and physical interventions, there is a constant need for developing additional approaches for optimizing rehabilitation gains. Mental imagery is an emerging field in neurorehabilitation and has the potential to serve as an adjunct therapy to enhance patient function. Yet, the literature on this topic is sparse. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 168 publications
(102 reference statements)
0
17
0
2
Order By: Relevance
“…Several cognitive pathways, such as attentional concentration and body schema, are used to ameliorate motor and non-motor symptoms. They found that motor imaging might help Parkinson’s sufferers’ motor functions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several cognitive pathways, such as attentional concentration and body schema, are used to ameliorate motor and non-motor symptoms. They found that motor imaging might help Parkinson’s sufferers’ motor functions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lesser impairment of the Imagery compared to general cognitive functioning in alcoholic participants may represent a resource for the residential rehabilitation program. MI is an emerging rehabilitative approach to enhance the motor and cognitive functions in neurorehabilitation ( 52 ). Research has shown that Imagery training leads to substantially improvements in memory performance in older adults ( 53 , 54 ) and in participants with Alzheimer's disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…MI is a key option for rehabilitation because this technique has a minimal risk of physical injury, a high level of accessibility, ease of availability, minimal financial cost, and minimal need for equipment. Moreover, this innovative technique based on explicit learning can target various motor and non-motor aspects of one’s performance [ 18 – 20 ]. Note that in the advanced stages of PD, when physical activity becomes intensively limited, MI is the recommended relevant technique.…”
Section: Introductionmentioning
confidence: 99%